Form-finding of surface in the form of enneper minimal surface / Hooi Min Yee and Kok Keong Choong - Hooi, Min Yee (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2012)
Form-finding is carried out for tensioned fabric structures in order to determine the initial equilibrium shape under a prescribed support condition and a pre-stress pattern. Experimental form-finding using soap film model is frequently used to investigate the possible forms of uniformly stressed surfaces. Soap film models also provide a means for checking the accuracy of computational form-finding results. In this study, a soap film model is used to determine the surface form corresponding to a boundary shape defined by the mathematical equation for Enneper minimal surface. The obtained soap film models are compared with the computational form-finding results for a certain range of parameters. The study shows that within certain limits of the parameters defining Enneper minimal surfaces, results of computational form-finding are in good agreement with mathematically defined Enneper minimal surfaces.